Proposals for integrated public management of the menopausal transition and postmenopause through Spanish women's experiences: a qualitative study - Selva, Clara (Frontiers in Reproductive Health, 2024)
IntroductionIn Spain, legislation protecting women during the menopausal transition and postmenopause is still in its early stages. For public policies to be effective, it is essential that their design, implementation, and evaluation actively involve women going through this stage. Only from their experience and perspective can the impact of measures be maximized and ensure that they truly respond to their needs and realities. The goal of this article is to identify and analyze proposals for action that public organizations in Spain could undertake to improve the management of and transition through menopause. On the basis of the initiatives identified through women's narratives, this study aims to establish a solid basis for the inclusion of future governmental policies and practices in Spain. Adapting to the economic conditions and sociocultural aspects specific to each region can stimulate reflection and debate on their policies regarding menopause.MethodsThis qualitative study, which was conducted in Spain, was based on 20 semistructured interviews with women who had experienced physiological and symptomatic menopause in the last five years, were postmenopausal, and were actively employed. The interviews were audio-recorded, transcribed, and analyzed following an inductive thematic analysis.ResultsThe stories of the interviewees indicate three categories of government action comprising a set of specific measures. More specifically, the categories relate to: (a) proposals for accompaniment and social awareness, (b) educational and training proposals, and (c) political and regulatory proposals.ConclusionsThis study identifies governmental proposals and specific actions to improve support for the menopausal transition and postmenopause in Spain. While its findings may be applicable to other countries, further research is needed to explore how they could be adapted to the different socioeconomic and cultural realities of those contexts. Ultimately, the proposals presented lay the groundwork for developing public policies and laws that respond to the needs of women, improving their well-being and promoting gender equity in public health.